Penelitian Hubungan Parameter Sensori (Demerit Point Score), Kimia, dan Mikrobiologi Pada Kemunduran Mutu Ikan Nila Selama Pengesan - Ariyani, Farida; Murtini, Jovita Tri (Jurnal Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
ABSTRACT: Research on the correlation of sensory (Demerit Point Score), chemical, and microbiological parameters during deterioration process of fresh tilapia stored in ice has been conducted. Live tilapia was killed by hypothermia method (immersing in ice water) and subsequently arranged in insulated box filled with flake ice with the ratio of ice and fish of 2:1 (w/w). The ice in boxes was checked and melted ice was replaced every day. The box was stored at ambient temperature andobservation on freshness changes of tilapia was done every 3 days for sensory (Demerit Point Scores/DPS), chemical (TVB, K value) and microbiological (TPC) qualities until the fish was rejected by panelists. Results of the experiment showed that after 15 days storage, fresh tilapia was still accepted by panelists, however, after being stored for 18 days, tilapia was unfit for human consumption with the value of DPS 25.9, TVB 48 mgN%, K value 76.4% and TPC 5.0 x 105 cfu. It was shown that DPS correlated well with TVB as well as K value but did not correlate well with total bacteria.